O estudo do crescimento de grão em uma liga Al-1 % massa Mn - Fonseca, Gláucio Soares da (2007)
Grain growth was studied in detail in a high purity Al-1mass% Mn alloy containing particles. This thesis contains an introduction, a literature survey, materials and methods and five chapters about: grain geometry, precipitate characterization, influence of the precipitates in the grain boundary pinning, abnormal grain growth and the effect of thickness on grain growth. In chapter 4, grain geometry, the measures of the three grain curvatures are presented. Geometrical models relating these three quantities to the mean intercept length of the grains, l, were derived. The models showed good agreement with experimental data. After precipitate characterization done in chapter 5, the influence of the precipitates on grain boundary pinning was studied in chapter 6. The usual expression to calculate the limiting or critical grain radius due to the pinning by precipitates uses quantities that are not very convenient for comparison with experimental results. In this work two alternative expressions are proposed. Good agreement is obtained between theory and experiments. The relative merits and shortcomings of each expression are discussed in detail from a fundamental and experimental point of view. During abnormal grain growth, in contrast with the normal grain growth, only few large grains dominate the grain growth process. Chapter 7 deals with the evolution of the abnormal grains and the influence of these grains in the normal grains geometry. In chapter 8, the effect of thickness on grain growth and on the geometry of grains was studied. Finally the work was summarized and its main conclusions were presented.